LIFESTYLING DALAM PEMBENTUKAN ULANG TUBUH PRIA URBAN GOLONGAN BAWAH (STUDI KASUS âPUSAT KEBUGARAN TUBUHâ GORILLA POWER BODY BUILDING, GANG BUNTU, SEMARANG, JAWA TENGAH) - , Krisetiawati Puspitasari, Dr. Budiawan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to discuss on how lower class urban men like paddicab drivers, porters, construction workers, security guards, and cleaning service crew among others, embrace lifestyling upon fitness lifestyle. In Indonesia, fitness lifestyle is introduced by fitness centre through lifestyle magazines. The concept of lifestyling derives from Solvay Gerke (2000). It is understood as a behavior of showing off a certain lifestyle without the support of economic capability which is the fundamental basis of consumption. Therefore, lifestyling is only based on the sheer symbolic dimension of a consumtive practice without the support of economic capability. This research is based on the case study of âGorilla Power Body Buildingâ at Gang Buntu in Semarang that could be notified as fitness club for a lower-class urban men. The research shows that lifestyling to some extent could be considered as a resistance against the fitness lifestyle regime. It is proven tha muscular body which has been a sort of an ideal in the fitness lifestyle could easily be gained with a very simple dan hand made fitness equipment, a different kind of exercise, and a non-dietary meal. However, the ideal shape is not exactly the same as that of the urban men from the middle and high classes. The lower class urban men have chosen this fitness lifestyle because the have desire to become the urban men of the middle and high classes. Through their newly body shape, the narrate their identity that is different from the other menâs of the same class. In this case, the make class-passing as if the were on the upper class, although in reality the remain in the same class.